Alfaxalone total intravenous anaesthesia in dogs: pharmacokinetics, cardiovascular data and recovery characteristics. (September 2019) - Dehuisser, Virginie; Bosmans, Tim; Devreese, Mathias; Gehring, Ronette; Croubels, Siska; Duchateau, Luc; Polis, Ingeborgh
Abstract: Objective: To evaluate the cardiovascular effects, pharmacokinetic (PK) data and recovery characteristics of an alfaxalone constant rate infusion (CRI) of different duration in dogs at manufacturer's recommended dose rate. Study design: Experimental, prospective, randomized, crossover study. Animals: Six intact female Beagles. Methods: Following an intravenous alfaxalone bolus (3 mg kg –1 ), anaesthesia was maintained using an alfaxalone CRI at 0.15 mg kg –1 minute –1 for 90 (short CRI) or 180 minutes (long CRI). Venous blood samples were collected to determine the PK profile. Cardiovascular variables and recovery characteristics were evaluated. Recovery was scored on a scale ranging from 0, excellent to 4, bad. A mixed-model statistical approach was used to compare the cardiovascular parameters (global α = 0.05). An analysis of variance was performed to compare PK parameters and recovery times between treatments. Results: No significant difference was noted between protocols for any PK parameter. Volume of distribution at steady state (935.74 ± 170.25 versus 1119.15 ± 190.65 mL kg –1 ), elimination half-life (12 ± 2 versus 13 ± 3 minutes), clearance from the central compartment (26.02 ± 4.41 versus 27.74 ± 5.65 mL kg –1 minute –1 ) and intercompartmental clearance (8.47 ± 4.06 versus 12.58 ± 7.03 mL kg –1 minute –1 ) were comparable for short CRI and long CRI. Cardiovascular variables remained within physiological limits. Mechanical ventilation was necessary (short CRI: n = 1, long CRI: n = 4). The manufacturer's recommended dose rate resulted in a light plane of anaesthesia. No significant differences in recovery times and scores were observed between treatments. The quality of recovery was scored as very poor with both protocols. Conclusions and clinical relevance: PK data were similar between long and short infusions of alfaxalone at the manufacturer's recommended dose, with acceptable cardiovascular conditions. Nevertheless, both protocols resulted in a superficial plane of general anaesthesia with poor recovery characteristics.